2014
DOI: 10.1021/cb500552f
|View full text |Cite
|
Sign up to set email alerts
|

MitoBlue: A Nontoxic and Photostable Blue-Emitting Dye That Selectively Labels Functional Mitochondria

Abstract: We report the discovery of a fluorogenic dye, N1,N3-di(2-aminidonaphthalen-6-yl) propane-1,3-diamine, MitoBlue, which selectively stains functional mitochondria while displaying low toxicity, bright blue emission, and high resistance to photobleaching. Additionally, we show that a biotin-labeled MitoBlue derivative can be used as a handle for the delivery of streptavidin-tagged species to the mitochondria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 49 publications
(77 reference statements)
1
10
0
Order By: Relevance
“…9 However, because TPP and most therapeutic drugs are nonemissive, additional conjugation of a fluorescent moiety is usually required to enable the monitoring of mitochondria‐specific drug delivery, which may disturb interactions between drugs and molecular targets, resulting in reduced therapeutic efficacy. An alternative approach demonstrated recently is the direct use of mitochondria‐targeted fluorophores to build fluorescent theranostic probes 10. Compared with the nonfluorescent TPP tag, mitochondria‐targeted fluorophores offer the potential for direct visualization of their intracellular delivery under fluorescence microscopy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 However, because TPP and most therapeutic drugs are nonemissive, additional conjugation of a fluorescent moiety is usually required to enable the monitoring of mitochondria‐specific drug delivery, which may disturb interactions between drugs and molecular targets, resulting in reduced therapeutic efficacy. An alternative approach demonstrated recently is the direct use of mitochondria‐targeted fluorophores to build fluorescent theranostic probes 10. Compared with the nonfluorescent TPP tag, mitochondria‐targeted fluorophores offer the potential for direct visualization of their intracellular delivery under fluorescence microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach demonstratedr ecently is the direct use of mitochondria-targeted fluorophores to build fluorescent theranostic probes. [10] Compared with the nonfluorescent TPP tag,m itochondria-targeted fluorophores offer the potentialf or direct visualization of their intracellulard eliveryu nder fluorescence microscopy. For example,X ie et al reported an ovel fluorescentb oron dipyrromethene (BODIPY)-platinum conjugate that proved to localize predominantly in the mitochondria, and exhibited high cellular proliferation inhibition against humanc ervical carcinoma (HeLa) and humanb reast cancer( MCF-7) cells.…”
Section: Introductionmentioning
confidence: 99%
“…[9,20,21] Bisbenzamidines are known to bind to the minor grooves of adenine/thymine-rich double-strandD NA. [22,23] Moreover,b enzamidine moieties present prominenta rgininem imetics and have often been used to address the S1 binding site of trypsin-like serine proteases. [24][25][26] In particular,d ibasic compounds containing at least one benzamidine substructure have been reported as potent inhibitors of trypsin, thrombin, factor Xa, matriptase and matriptase-2, indicating that severalb inding pockets within the active sites of these enzymes can be addressedb yb asic moieties.…”
Section: Introductionmentioning
confidence: 99%
“…Another derivative of bis(4-aminostyryl) naphthalene exhibits a pronounced fluorescence and strong affinity for fibers and for that reason it was used as an optical brightener for improving the whiteness of materials [33]. The literature reports also indicate applications of fluorescent naphthylamines and aminidonaphthalic derivatives as fluorescent dyes in cell imaging [34,35].…”
Section: Introductionmentioning
confidence: 99%